Pengenalan Teknologi Pengolahan Limbah Plastik sebagai Upaya Pemberdayaan Masyarakat di Desa Gading Watu, Gresik - Granita Hajar; Desita Nur Rachmaniar; Aufar Fikri Dimyati; Ahmad Maulana Muchtar; Rara Ayu Nathania Swasti; Ronalda Giovani Nipun Sitorus; Ratu Fajar Diva Malika Bahagia; Adi Candra (Universitas Pahlawan Tuanku Tambusai, 2026)
The problem of household plastic waste remains an environmental challenge in various regions, including Gading Watu Village, Menganti District, Gresik Regency. This community service program aims to introduce a simple technology for processing plastic bottle waste through a heating process to form liquid plastic that can be formed as the initial stage of plastic waste recycling. The implementation method includes a community needs survey, design and testing of plastic processing equipment, training on melting and forming plastic, and socialization of the environmental impacts of plastic waste. The results of the activity show an increase in community understanding and basic skills in plastic waste management, although the technology and processed products still require further development. This program is expected to be the first step in building community awareness and independence in sustainable plastic waste management.